Frame-filling C/C composite for high-performance EDLCs with high withstanding voltage. (May 2018) - Chang, Pan-pan; Wang, Cheng-yang; Kinumoto, Taro; Tsumura, Tomoki; Chen, Ming-ming; Toyoda, Masahiro
Abstract: Based on the equation of E = 1/2CV 2, increasing voltage can significantly enhance the energy density of electric double-layer capacitors (EDLCs). However, with the voltage above 2.7 V, the lifespan of EDLCs drops rapidly due to the undesired parasitic processes. To operate at voltage above 2.7 V, a frame-filling C/C composite is prepared by constructing relatively perfect carbon network and reducing the oxygen-containing groups. The as-prepared sample F310-800 exhibits high specific surface area (2626 m 2  g −1 ), adequate e -conductivity (142 S m −1 ), high sp 2 -bonding carbon content (92.6%) and low oxygen content (4.6  wt %). Although totally free of any carbon black, it demonstrates excellent EDLC performances. It can successfully operate at voltage of 3 V in TEABF4 /PC electrolyte and obtain high gravimetric capacitance ( C g ) of 140 F g −1 and volumetric capacitance ( C v ) of 57.4 F cm −3 at 50 mA g −1 with rate capacity C10/0.05 as high as 66%. Additionally, at voltage of 3.5 V in pure EMIMBF4 electrolyte, it achieves ultrahigh C g of 156 F g −1 and C v of 64 F cm −3 at 50 mA g −1 . Its energy density can reach up to 66.3 Wh kg −1 . Meantime, after 5000 cycles at 2.5 A g −1, it holds 91.9% of its initial capacitance. Graphical abstract: Image 1